2015
DOI: 10.1007/s00784-015-1479-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of zirconia-based implant- and tooth-supported single crowns

Abstract: The zirconia-based single crowns can be used clinically for tooth- and implant-supported restorations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
23
0
6

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 38 publications
3
23
0
6
Order By: Relevance
“…Previous publications evaluating the same material composition (Cercon/Cercon Ceram Kiss; DeguDent, Hanau, Germany) in a comparable setup found significantly higher complication rates of 7.5% after 6 months and 24.5% after two years, respectively [9,23]. Furthermore, the patient-reported outcome was assessed in this trial [22], revealing a high patient satisfaction, as observed in the present investigation. However, the patients were surveyed only once after the treatment.…”
Section: Patient-reported Outcome (Vas)supporting
confidence: 83%
See 1 more Smart Citation
“…Previous publications evaluating the same material composition (Cercon/Cercon Ceram Kiss; DeguDent, Hanau, Germany) in a comparable setup found significantly higher complication rates of 7.5% after 6 months and 24.5% after two years, respectively [9,23]. Furthermore, the patient-reported outcome was assessed in this trial [22], revealing a high patient satisfaction, as observed in the present investigation. However, the patients were surveyed only once after the treatment.…”
Section: Patient-reported Outcome (Vas)supporting
confidence: 83%
“…Hence, the provided data on the technical outcome can be considered comparable to our results. In a retrospective study, Nejatidanesh and co-workers evaluated 232 cemented implant-supported SCs placed in 122 patients after a mean exposure time of 59.2 months [22]. Fracture of the veneering ceramic occurred in 8.2% of the restorations (n = 19; 7 anterior, 12 posterior), and two replacements were necessary.…”
Section: Patient-reported Outcome (Vas)mentioning
confidence: 99%
“…To cover this risk the authors suggested full‐cast metal or monolithic zirconia crowns as possible options for crowns located on terminal abutments . Nejatidanesh and colleagues re‐examined 142 anterior and 182 posterior tooth‐supported single crowns after a mean of 60.7 months and calculated cumulative ceramic fracture‐free survival of 91% . The incidence of chipping was significantly ( p = 0.004) higher for molar and anterior crowns than for premolars .…”
Section: Discussionsupporting
confidence: 38%
“…The incidence of chipping was significantly ( p = 0.004) higher for molar and anterior crowns than for premolars . This was ascribed to larger occlusal forces in the posterior region and an unfavorable load direction for anterior teeth . In comparison with these studies, in the present study mechanical stability of the restoration material was superior: fracture‐free survival was 98.5% for PZCs (60.6% located in the anterior region) and 100% for MZCs (96.6% located in the posterior region).…”
Section: Discussionmentioning
confidence: 98%
“…Of these implant failures, 15 occurred before prosthesis insertion(Bömicke, Gabbert, Koob, Krisam, & Rammelsberg, 2017;Bonde et al, 2010;Malo et al, 2015;Spies, Stampf, et al, 2015), 44 after prosthesis insertion(Bergenblock et al, 2012;Cionca et al, 2015;Cooper et al, 2016;Guarnieri, Ceccherini, & Grande, 2015;Malo et al, 2015;Nejatidanesh, Moradpoor, & Savabi, 2016;Payer et al, 2015;Spies, Stampf, et al, 2015;Worni, Kolgeci, Rentsch-Kollar, Katsoulis, & Mericske- Stern, 2015;Worni et al, 2017), and four(Nothdurft, Nonhoff, & Pospiech, 2014;Payer et al, 2013; at undefined time points. Of these implant failures, 15 occurred before prosthesis insertion(Bömicke, Gabbert, Koob, Krisam, & Rammelsberg, 2017;Bonde et al, 2010;Malo et al, 2015;Spies, Stampf, et al, 2015), 44 after prosthesis insertion(Bergenblock et al, 2012;Cionca et al, 2015;Cooper et al, 2016;Guarnieri, Ceccherini, & Grande, 2015;Malo et al, 2015;Nejatidanesh, Moradpoor, & Savabi, 2016;Payer et al, 2015;Spies, Stampf, et al, 2015;Worni, Kolgeci, Rentsch-Kollar, Katsoulis, & Mericske- Stern, 2015;Worni et al, 2017), and four(Nothdurft, Nonhoff, & Pospiech, 2014;Payer et al, 2013; at undefined time points.…”
mentioning
confidence: 99%